Pengaruh Free Shipping dan Shopping Lifestyle Terhadap Impulse Buying pada Tiktok Shop - Alpya, Novella; Pramuditha, Charisma Ayu (MDP Student Conference, 2025)
This study aims to analyze the effect of free shipping and shopping lifestyle on impulse buying among TikTok Shop platform users. The research employs a quantitative method with a purposive sampling technique, using the Slovin formula to determine the sample size, involving 400 respondents from Generation Z and Millennials in Palembang City. Hypothesis testing was conducted using multiple linear regression analysis with SPSS 26. The results indicate that free shipping has a positive and significant effect on impulse buying, suggesting that waived shipping fees can encourage impulsive purchases. Additionally, shopping lifestyle also has a positive and significant effect on impulse buying, implying that a person's consumption patterns and shopping habits contribute to unplanned purchasing decisions. In conclusion, free shipping and a high shopping lifestyle tendency can increase the likelihood of impulse buying on the TikTok Shop platform.